Regional fractional ventilation mapping in spontaneously breathing mice using hyperpolarized 129Xe MRI. (14th October 2014) - Imai, Hirohiko; Matsumoto, Hironobu; Miyakoshi, Erika; Okumura, Shintaro; Fujiwara, Hideaki; Kimura, Atsuomi
<x xml:space="preserve">Abstract</x> The feasibility of ventilation imaging with hyperpolarized (HP) 129Xe MRI has been investigated for quantitative and regional assessment of ventilation in spontaneously breathing mice. The multiple breath ventilation imaging technique was modified to the protocol of spontaneous inhalation of HP 129Xe delivered continuously from a 129Xe polarizer. A series of 129Xe ventilation images was obtained by varying the number of breaths before the 129Xe lung imaging. The fractional ventilation, r, was successfully evaluated for spontaneously breathing mice. An attempt was made to detect ventilation dysfunction in the emphysematous mouse lung induced by intratracheal administration of porcine pancreatic elastase (PPE). As a result, the distribution of fractional ventilation could be visualized by the r map. Significant dysfunction of ventilation was quantitatively identified in the PPE‐treated group. The whole‐lung r value of 0.34 ± 0.01 for control mice (N = 4) was significantly reduced, to 0.25 ± 0.07, in PPE‐treated mice (N = 4) (p = 0.038). This study is the first application of multiple breath ventilation imaging to spontaneously breathing mice, and shows that this methodology is sensitive to differences in the pulmonary ventilation. This methodology is expected to improve simplicity as well as noninvasiveness when assessing regional ventilation in small rodents. Copyright © 2014 John Wiley & Sons, Ltd.